KOMPETENSI GURU DALAM MELAKSANAKAN DAN MENGELOLA PROSES BELAJAR MENGAJAR DI PONDOK PESANTREN DARUL MURSYIDI DESA SIALOGO TAPANULI SELATAN - Darliana Sormin (IAIN Padangsidimpuan, 2016)
This study discusses the competence of teachers in implementing and managing learning in Pon-pes Darul Mursyidi. The purposes of this study were to determine the competence of teachers in managing learning in Pon-pes Darul Mursyidi and to know the efforts of teachers in managing learning in Pon-pes Darul Mursyidi. The research method used is descriptive qualitative method while the data collection techniques used were interviews, observation and documentation, and the analysis of data by compiling the data, organizing the data, then describing systematically. The results of the competency of teachers in implementing and managing learning in Pon-pes Darul Mursyidi've started well although still have problems, all the planning and implementation process of learning have applied maximally by teachers at Darul Ponpes Mursyidi. Then, the efforts are being made in the establishment of the competency of teachers by suggesting continuing education to a higher level, following the seminars, training, or workshops, and reading relevant books to broaden the knowledge and competence.